DEVELOPING A MULTI-ITEM, MULTI-PRODUCT, AND MULTI-PERIOD SUPPLY CHAIN NETWORK DESIGN AND PLANNING MODEL FOR PERISHABLE PRODUCTS - Al-Ashhab, M. S.; Alanazi, Fahad (International Journal of Research -GRANTHAALAYAH, 2022)
Background/Objectives: In this paper, a sustainable supply chain network design and planning model is developed for perishable products. The model aims to maximize total profit in addition to preventing the expiration of perishable products using the FIFO inventory strategy to reduce environmental impact by reducing waste. Methods/Statistical Analysis: A mathematical model is developed to design a sustainable, multi-item, multi-product, multi-period, three-echelon supply network including three potential suppliers, three potential factories, a warehouse, and three retailers. The model is formulated as mixed-integer nonlinear programming. It is solved by DICOPT/GAMS. Findings: The behavior of the model has been verified by solving six scenarios of different demand patterns. The results verify the ability of the developed model in assisting the SC organizations to manage their network more efficiently Novelty/Applications: The model considered the production, inventory, and transportation of two perishable products in multi-periods. It maximizes the profit in addition to preventing the expiration to minimize environmental impact to ensure sustainability of the supply chain. The model is solved by DICOPT/GAMS.